2006
DOI: 10.1016/j.phytochem.2006.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma – A therapeutic fungal biofactory

Abstract: Ganoderma is a basidiomycete white rot fungus which has been used for medicinal purposes for centuries particularly in China, Japan and Korea. A great deal of work has been carried out on Ganoderma lucidum. The common names for preparations include Lingzhi, Munnertake, Sachitake, Reishi and Youngzhi. This review collates the publications detailing activities and compounds by representative species whilst considering the most valid claims of effectiveness. The biological activities reported of preparations from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
366
0
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 737 publications
(383 citation statements)
references
References 114 publications
(109 reference statements)
3
366
0
14
Order By: Relevance
“…Further, it has been reported to have antioxidant, anti-inflammatory, antitumor, antihypertensive, antihistaminic and antihepatotoxic effects. Cytotoxic triterpenoids and immunomodulating polysaccharides are the major chemical constituents of G. lucidum (5). In vitro studies showed that the administration of polysaccharides isolated from G. lucidum spores could effectively inhibit growth in mice with transplanted S180 sarcoma (6).…”
mentioning
confidence: 99%
“…Further, it has been reported to have antioxidant, anti-inflammatory, antitumor, antihypertensive, antihistaminic and antihepatotoxic effects. Cytotoxic triterpenoids and immunomodulating polysaccharides are the major chemical constituents of G. lucidum (5). In vitro studies showed that the administration of polysaccharides isolated from G. lucidum spores could effectively inhibit growth in mice with transplanted S180 sarcoma (6).…”
mentioning
confidence: 99%
“…1) More than one hundred species of bioactive components have been isolated from G. lucidum, 2) such as polysaccharides, triterpenoids and alkaloids, in which that Ganoderma lucidum polysaccharide (GLPS) is one of the major active components. Its multiple pharmacological effects, such as antitumor, 3) antioxidation, 4) immunomodulation 5,6) and especially hepatoprotection against chemical or immune hepatic damage, 4,7) have been demonstrated in many animal models in vivo and in vitro.…”
mentioning
confidence: 99%
“…9) However, whether P450 down-regulation is a homeostatic mechanism or a pathophysiological phenomenon has not been elucidated. On the other hand, because G. lucidum is currently popularly used as self-medication in East Asia, 1) thus, it is needed to be investigated that whether GLPS influences P450 metabolic activity.…”
mentioning
confidence: 99%
“…has been used for treatment in various diseases over a long period (Paterson 2006). Our review clearly showed that compounds from Ganoderma sp., under the extensive in vivo and pharmacological research, can be used in various microorganisms and parasitic diseases.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…A search for “Ganoderma” in the database Index Fungorum displayed 409 species records, including synonyms (http://www.speciesfungorum.org). Ganoderma sp., especially G. lucidum, G. tsugae and G. applanatum, are well studied and have been in use in East Asian countries since the ancient times for the treatment of various diseases (Ofodile et al 2005; Paterson 2006; Ferreira et al 2015). Triterpenes and polysaccharides are considered key constituents isolated from fruiting bodies, gills, spores and mycelia for their bioactivities (Xia et al 2014).…”
Section: Introductionmentioning
confidence: 99%